Oscillator Pond: Analog Critters in a Digital Pool. An Ambient and Interactive Audio Installation. - Moses, James (Contemporary Music Review, 2017)
Drawing on my current research, I discuss a site-specific project developed as part of an environment art-science program, Atmospheres, whereby a randomized soundscape was introduced into a greenhouse. Organic sounding rhythms and creature-like tones were generated on a restored synthesizer, an ARP 2500, made in the 1970s, and were then captured digitally. The critter sounds are triggered with custom software using probability and random processes to create a surreal and unpredictable soundscape that changes through the day. Visitors can interrupt this ‘organic mode’ to hear specific critter sounds and activate some special playback modes.